Navigating a turbulent career path without alienation: The mediating role of work-related rumination and the moderating effect of information literacy - Ao, Rong; Chen, Chun-Shuo (Edelweiss Applied Science and Technology, 2026)
Against the backdrop of frequent industrial restructuring and accelerated technological iteration, career insecurity has become a critical stressor affecting organizational stability and individual mental health. Grounded in stress and coping theory, this study develops a moderated mediation model to examine how career insecurity shapes employees’ work alienation, as well as testing the mediating role of work-related rumination and the moderating effect of information literacy. Using snowball sampling, survey data are collected from 512 employees in first-tier, emerging first-tier, and provincial capital cities. Empirical results indicate that career insecurity positively predicts work alienation, work-related rumination mediates this relationship, and information literacy negatively moderates the path from career insecurity to work-related rumination. The findings deepen the theoretical understanding of the formation mechanisms of negative work attitudes in the digital era. Moreover, by enhancing employees’ information literacy and optimizing stress management strategies, the study offers practical guidance for organizations seeking to reduce work alienation.